The Literature of Tatar Children: The Formation and Definition of Content - Gulnar V. Yuldybaeva4, Alfira S. Hajrullina5Liailia I. Mingazova1, Fanuza H. Gabdrakhmanova2, Gumar F. Dautov3, (Opción, 2019)
The article is devoted to the definition of the essence of Tatar children’s literature via comparative qualitative research methods. As a result, the study of materials relating to the formation of children’s literature, made it possible to get an idea of its essential manifestations, its originality, its significance in the general literary process. In conclusion, the aspects selected on the basis of systematization of studies of children’s literature allow us to formulate the definition of children’s literature as a special subsystem of literature that focuses on dialogue with consciousness of children and reproduces the subculture of child in codes characteristic.